Medicine in novel technology and devices - Beijing Advanced Innovation Center for Biomedical Engineering (Elsevier B.V, 2019)
Medicine in Novel Technology and Devices is a peer-reviewed open access journal. The journal publishes cutting-edge approaches, techniques and instruments which serve in medical purpose. It focuses the application of those technologies and devices in human health, including disease prevention, diagnosis, treatment, prognosis, monitoring and nursing, rehabilitation.
Keywords: Medical technology : Periodicals; Medical innovations : Periodicals; Medical instruments and apparatus : Periodicals; Biomedical Technology; Equipment and Supplies; Inventions; Medical innovations; Medical instruments and apparatus; Medical technology